Tomber juste - N. Strobbe (Law Text Culture, 1998)
This name no longer names Jean-Francois Lyotard. A name which can no longer speak in our idiom, an absolutely different name, a diffirend. How to remember the unpresentable? What time belongs to this temporality; this passing that has been, and that goes under to his name (with which we are out of touch, and which left in the historicity of a touch, leaving touch, dis-sensus)?